Analysis of Related Documents using Text Mining - Pethunachiyar, G. A. (International Journal of Advanced Science and Technology, 2020)
Nowadays, Artificial Intelligence (AI) becomes the wide-spread  technique in analyzing huge data.  AI is used in analyzing the unstructured documents to extract the structured information with the help of Natural Language Processing. This paper gives the importance of text mining and the current status of the research in text mining. The objective of the paper is to extract the information from the collected documents that are related to each other. The Collected documents are related to the wireless technologies and mobile commerce. From the selected documents , the frequently occurred words are identified and analyzed. The result shows that the frequently occurred words in all the documents are related and it shows its importance in the document.